(untitled) (American Journal of Islam and Society, 2003)
"Terrorism expert" Steven Emerson has done it again. With his usual exaggerated style and hate-mongering rhetoric, Emerson has painted all Muslims with the same broad brush. While trying to assure his readers at the outset that not all Muslims are terrorists, the bulk of his new book, American Jihad, is filled with brazenly over-simplified attacks on the entire Muslim American community. This biased and heavy-handed portrayal of Muslims is characteristic of Emerson’s work - most notably his 1994 PBS video "Jihad in America." In American Jihad, Emerson again presents a terrifying picture of American Muslims as fanatical, violent people lurking and plotting against the United States. It is thus hardly surprising that he has gained a reputation, reminiscent of his friend Daniel Pipes, for advocating grand Islamic conspiracies without any credible evidence. In a rush to get to press, his latest book is a quick tabloid-style read. The book is divided into eight chapters. The first chapter deals with Emerson’s "discovery" of"militant Muslims" and the subsequent making of his PBS video "Jihad in America." The next six chapters attempt to uncover the inner working of such groups as the Council on AmericanIslamic Relations (CAIR), Hamas, and al-Qaida. He also spends one entire chapter on the terrorist infiltration of American academic institutions. Finally, in his concluding chapter, Emerson tries to encourage individuals within the Muslim community to "fight back" against the threat that he feels is facing the country. The book is large on print and short on analysis. For a decade, Emerson has been issuing dire, over-the-top warnings that Muslims in the United States pose a catastrophic threat to the country, and in this book ...